To solve the factored quadratic equation \((13x + 3)(9x - 14) = 0\), we set each factor to zero and solve for \(x\):
-
First factor: \[ 13x + 3 = 0 \] Subtract \(3\) from both sides: \[ 13x = -3 \] Now, divide by \(13\): \[ x = -\frac{3}{13} \]
-
Second factor: \[ 9x - 14 = 0 \] Add \(14\) to both sides: \[ 9x = 14 \] Now, divide by \(9\): \[ x = \frac{14}{9} \]
Now, we can write the solution set \(x = \left{-\frac{3}{13}, \frac{14}{9}\right}\).
The correct response from the provided options is:
The solution set is \(x = \left{-\frac{3}{13}, \frac{14}{9}\right}\).